ANALISIS KEPATUHAN PEMENUHAN KEWAJIBAN PERPAJAKAN PADA RSUD ABDUL WAHAB SJAHRANIE SAMARINDA - Nurul Jannah; Yunus Tete Konde; Dhina Mustika Sari (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
The purpose of this study is to find out the compliance of taxation of Article 22 Income Tax and VAT of RSUD Abdul Wahab Sjahranie viewed from the side of Calculation, Collection, Depositing and Reporting and comparing the procedure of calculation, collection, tax and reporting of Income Tax Article 22 and VAT by RSUD Abdul Wahab Sjahranie with Law number. 36 of 2008, Law number  42 of 2009 and other implementing regulations used as an analytical tool of this research. The method of analysis that used in this study was comparative descriptive analysis, and to obtain the data in this research the authors collect data by through documentation and library data. The results of the analysis show that the calculation, collection and tax payment were in accordance with Law number 36 of 2008 and Law number 42 year 2009. Tax reporting still happened delay which caused RSUD Abdul Wahab Sjahranie to be subject to sanction of delay on tax reporting.Keywords: Calculation, Collection, Deposit, Reporting, Income Tax Article 22, VAT